East versus West: Impact of Geopolitical Shocks on European Sovereign Yields - Panciriovaitė, Rytė; Jurkšas, Linas (Ekonomika, 2026)
How do geopolitical factors ripple through the European sovereign bond yields? And does this effect differ between Eastern and Western European markets? These two crucial, but not yet fully answered questions motivated us to investigate the link between geopolitical factors and sovereign bond yields in Eastern and Western Europe. We thus leverage a panel dataset covering 16 European countries from 2015 to 2025, both at daily and monthly frequencies. The first set of panel regression models revealed that rising geopolitical tensions exert a robust, direct and statistically significant effect on sovereign yields even with a lag. The second set of panel models undercover that this effect is much stronger in Eastern Europe than in the Western European region. This gap persists across frequencies and model specifications, thus highlighting the heightened vulnerability of less liquid, lower-rated Eastern markets. These and other findings in the study could help investors adjust their portfolios more effectively in response to geopolitical shocks, and assist supervisors in safeguarding financial stability.